2023
DOI: 10.1186/s12906-023-04000-0
|View full text |Cite
|
Sign up to set email alerts
|

A whole transcriptome profiling analysis for antidepressant mechanism of Xiaoyaosan mediated synapse loss via BDNF/trkB/PI3K signal axis in CUMS rats

Abstract: Background Depression is a neuropsychiatric disease resulting from deteriorations of molecular networks and synaptic injury induced by stress. Traditional Chinese formula Xiaoyaosan (XYS) exert antidepressant effect, which was demonstrated by a great many of clinical and basic investigation. However, the exact mechanism of XYS has not yet been fully elucidated. Methods In this study, chronic unpredictable mild stress (CUMS) rats were used as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…In our study, our study found that CUMS caused a decrease in dendrite length and spinal density in rats. This is similar to the results of some studies in recent years, CUMS induced the decrease of dendrite length and spinal density in the brain region of depressed rats 6,22–25 . Hei et al.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, our study found that CUMS caused a decrease in dendrite length and spinal density in rats. This is similar to the results of some studies in recent years, CUMS induced the decrease of dendrite length and spinal density in the brain region of depressed rats 6,22–25 . Hei et al.…”
Section: Discussionsupporting
confidence: 92%
“…The rats were placed individually in an unfamiliar open field box (80 cm × 80 cm × 60 cm) and allowed to freely explore for 5 min (Meng et al., 2023 ). Their spontaneous activity within the past 5 min was recorded using an automated video tracking system (Smart V3.0, Panlab).…”
Section: Methodsmentioning
confidence: 99%